دور العمل الشرطي في الحد من الجريمة الالكترونية دراسة ميدانية بولاية تبسة - عماد بلغيث (University of M'Sila, 2025)
هدفت الدراسة إلى إبراز دور العمل الشرطي في الحد من الجريمة الإلكترونية من خلال التركيز على الآليات التي تعتمدها وحدات الشرطة المختصة في مكافحة هذا النوع من الجرائم، إضافة إلى التحديات والعراقيل التي تواجهها في الميدان. بالاعتماد على المنهج الوصفي التحليلي مدعومًا بأداة الملاحظة غير المشاركة والمقابلة مع عينة قصدية من عناصر الشرطة بولاية تبسة (رئيس مصلحة، ضباط، أعوان، ومفتش)، باعتبارها الجهة الرسمية المخولة قانونًا للتعامل مع الجرائم الإلكترونية. وقد سمح هذا المنهج بفهم طبيعة الممارسات الميدانية للشرطة، وأساليب البحث والتحري، وكيفية توظيف الأدوات القانونية والتنظيمية لمواجهة مظاهر الإجرام الرقمي. أظهرت نتائج الدراسة أن التدريب المتخصص في التحقيق الرقمي وتحليل البيانات يمثل حجر الأساس في مواجهة هذه الجرائم، إلى جانب الدور الحاسم للتشريعات الوطنية والدولية مثل قانون 09-04 والاتفاقية الأوروبية ببودابست. كما بيّن التحليل أن التعاون الدولي أصبح ضرورة لملاحقة الجرائم العابرة للحدود، وأن التوعية المجتمعية تساهم بدورها في الوقاية والحد من مخاطر الاحتيال والتصيد الإلكتروني. ومع ذلك، تظل الأجهزة الشرطية تواجه تحديات حقيقية مثل صعوبة جمع الأدلة الرقمية القابلة للإثبات أمام القضاء، ونقص الكفاءات البشرية المتخصصة، مما يستدعي تعزيز الاستثمار في البنية التحتية التقنية وتوسيع الشراكات مع القطاع الخاص والباحثين الأكاديميين.
The study aimed to investigate the role of police work in reducing cybercrime, with a focus on the mechanisms employed by specialized police units in combating this type of crime, as well as the challenges they face in practice. It relied on a descriptive-analytical method supported by non-participant observation and interviews with a purposive sample of police personnel in Tébessa (head of department, officers, agents, and an inspector), as the official body legally authorized to deal with electronic crimes. This approach allowed for a better understanding of police field practices, investigative methods, and the use of legal and organizational tools to confront digital crime. The findings revealed that specialized training in digital investigation and data analysis is the cornerstone of addressing such crimes, along with the crucial role of national and international legislation such as Law 09-04 and the Budapest Convention. The analysis further indicated that international cooperation has become indispensable for tackling cross-border crimes, while community awareness contributes to prevention and to reducing the risks of fraud and phishing. However, police institutions still face serious challenges, including the difficulty of collecting digital evidence admissible in court and the shortage of specialized personnel, which calls for greater investment in technical infrastructure and the expansion of partnerships with the private sector and academic researchers.
Keywords: جريمة، جريمة الكترونية، شرطة، فضاء رقمي، مجرم رقمي; crime; cybercrime; police; cyberspace; cybercriminal